Correlation between Biophysical Properties of Niosomes Elaborated with Chloroquine and Different Tensioactives and Their Transfection Efficiency - Myriam Sainz-Ramos; Ilia Villate-Beitia; Idoia Gallego; Nuseibah AL Qtaish; Margarita Menéndez; Laura Lagartera; Santiago Grijalvo; Ramón Eritja; Gustavo Puras; José Luis Pedraz (MDPI AG, 2021)
Lipid nanocarriers, such as niosomes, are considered attractive candidates for non-viral gene delivery due to their suitable biocompatibility and high versatility. In this work, we studied the influence of incorporating chloroquine in niosomes biophysical performance, as well as the effect of non-ionic surfactant composition and protocol of incorporation in their biophysical performance. An exhaustive comparative evaluation of three niosome formulations differing in these parameters was performed, which included the analysis of their thermal stability, rheological behavior, mean particle size, dispersity, zeta potential, morphology, membrane packing capacity, affinity to bind DNA, ability to release and protect the genetic material, buffering capacity and ability to escape from artificially synthesized lysosomes. Finally, in vitro biological studies were, also, performed in order to determine the compatibility of the formulations with biological systems, their transfection efficiency and transgene expression. Results revealed that the incorporation of chloroquine in niosome formulations improved their biophysical properties and the transfection efficiency, while the substitution of one of the non-ionic surfactants and the phase of addition resulted in less biophysical variations. Of note, the present work provides several biophysical parameters and characterization strategies that could be used as gold standard for gene therapy nanosystems evaluation.